VIDEOGAMES TOWARDS ENGLISH ABILITY OF THE PLAYERS: A STUDY OF PERSPECTIVES - Iqbal Arya; Armeria Wijaya; Linda Mayasari (PROCEEDING UMSURABAYA, 2024)
In this study, the researcher discussed the impact of videogames in "Videogames towards English ability of the player: A study of perspectives" The purpose of this research is to analyze the impact of videogame on a player's English ability while in-game from the perspective of the player. The subject of the study is 33 players who have played video games for more than 2 years or more. The data were analyzed based on Krashen's monitor theory. In analyzing the data, the researcher used quantitative research to find as many respondents as possible using a survey and then analyze it. The procedure of the research is: first the researcher spread the survey while looking for a player who has played video games for more than 2 years. Second, the researcher analyzes and sorts the answer from the survey. Third, make the conclusion based on the survey. The conclusion is that videogames do indeed have a positive impact on English ability from the perspective of the player